STABILIZATION OF A POORLY-GRADED SAND WITH CUT-BACK BITUMEN AND A SOIL-WATER SLURRY - Budihartanto, Eko
Deposits from floods volcanic are sources sand in Indonesia. Many can be used directly for construction activities, others require modification, particularly the size , they be . The objective of the research programme described in this thesis was to determine if a satisfactory road base material could be made by combining medium curing cut-back bitumen, poorly-graded sand and a slurry of water and soil. Four slurry combinations were investigated; for control purposes, a mix consisting of cut-back bitumen and sand only was also investigated. The sand sample was obtained from Cimalaka and individual particle sizes were separated and then recombined to meet the median of the Asphalt Institute's specification for sand-bitumen material. The median gradation has coefficients of uniformity and curvature of 7.2 and 0.6, respectively and hence can be classified as "poorly-graded". The soil was sampled at Tanjungsari and was classified as A-2-4 (AASHTO) and SC-SP (USCS). Marshall analysis was performed on various combinations of materials cured for periods of 10 and 30 days and the most satisfactory combination was found to be that containing 84.8% sand, 4.8% cut-back bitumen and a slurry made of 5.0% soil and 5.4% water. The material proportions are expressed as percentages by weight of the total mixture. A modified Marshall-immersion test and indirect tensile strength and resilient modulus tests were performed on specimens of this composition. The index of retained stability was found to be 79%, after immersion for 4 days in water at 25Â°C. The influence of temperature and curing time on the indirect tensile strength of the material is relatively insignificant. The reduction in resilient modulus as temperature is increased is more significant at the longer curing period. Resilient modulus is increased considerably, particularly at lower temperatures, when curing period is increased from 10 to 30 days. All of the mix combinations investigated satisfy the ASPHALT INSTITUTE (1975) criteria for a sand-bitumen roadbase. However the composition identified as being most satisfactory meets, in addition, criteria that have been established by other investigators.